Dengue dasboard for forecasting the future trend of dengue cases in Pahang using auto regression integrated moving average (ARIMA) model - Muhammad Khairul Syafiq, Mustafa; Junaida, Sulaiman (2021)
The case study of this project is focuses on developing a dengue dashboard for forecasting the future trend of dengue cases in Pahang from 2021 to 2023 using ARIMA model. This dashboard also includes the latest information regarding the total number of dengue cases in Pahang, total deaths caused by dengue in Pahang, total cases according to each district in Pahang, interactive map of dengue cases in Pahang and a graph displaying the future trend of dengue cases.